The Cost and Benefits of Tax Treaties with Investment Hubs : Findings from Sub-Saharan Africa - Beer, Sebastian (IMF Working Papers; Working Paper ;, 2018)
This paper investigates the costs and benefits of concluding double tax treaties with investment hubs. Based on a sample of 41 African economies from 1985-2015, the results suggest that signing treaties with investment hubs is not associated with additional investments; yet, these treaties tend to come with nonnegligible revenue losses. Building on a theoretical model, the paper investigates the role of treaty shopping in driving nominal investment flows and provides indirect evidence for its importance in the sample.